Utility of Cell Block Preparation From CT-Guided FNAC with Immunohistochemistry in Diagnosing Primary Lung Carcinoma: A Prospective Study in A Tertiary Care Hospital - Mandal, Subhargha; Chowdhury, Abhishek; Bhattacharyya, Riju; Bhattacharyya, Palas (National Journal of Medical Research, 2025)
Introduction: Lung cancer remains a leading cause of cancer mortality globally, making early diagnosis critical. While core needle biopsy provides tissue samples, it carries risks including pneumothorax and hemothorax. Fine needle aspiration cytology offers a safer alternative with negligible complications. Cell block preparation can improve diagnostic accuracy of cytological specimens. Limited research exists on cell block utility with immunohistochemistry for primary lung cancer diagnosis. Materials and Methods: This prospective observational study evaluated cell block efficiency versus conventional cytological smears. One hundred twenty patients with CT-guided fine needle aspiration specimens underwent both conventional smear and cell block preparation. Immunohistochemical staining using TTF-1, p63, and synaptophysin was performed on cell block sections. Results were correlated with histopathological findings. Results: Cell block with immunohistochemistry demonstrated sensitivity of 95.4% (95% CI: 89.2-98.5%) and specificity of 91.2% (95% CI: 82.1-96.3%). Positive and negative predictive values were 96.5% (95% CI: 91.0-99.0%) and 88.6% (95% CI: 78.5-94.8%), respectively. Conclusions: Cell block preparation showed superior diagnostic performance compared to conventional smears alone. The combination of cell block immunohistochemistry with conventional cytology provides enhanced diagnostic accuracy for lung cancer evaluation. This approach can be routinely implemented for improved characterization of aspirated specimens.